2014
DOI: 10.4103/2231-0762.142002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of initial stability and crestal bone loss in immediate implant placement: An in vivo study

Abstract: Objectives:(1) To measure the crestal bone levels around implants immediately, and one month, three months, and six months after immediate implant placement, to evaluate the amount of bone level changes in six months. (2) To measure the initial stability in immediate implant placement.Materials and Methods:Ten patients were selected and a total of ten implants were placed in the immediate extraction sites. The change in the level of crestal bone was measured on standardized digital periapical radiographs taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Results from the present study showed an initial mean bone loss of 0.40 mm (SD = 0.48) after 6 months and minimal bone level changes over time up to 5 years in function. While the small sample size of this uncontrolled study limits direct comparisons to findings in other studies, these findings suggest that crestal bone loss around TM implants is lower than traditional titanium implant systems [13,14], and that the unique properties of PTTM may foster enhanced vital bone and surrounding tissue ingrowth and potentially reduce the amount of bone remodeling which occurs during the first year following implant surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…Results from the present study showed an initial mean bone loss of 0.40 mm (SD = 0.48) after 6 months and minimal bone level changes over time up to 5 years in function. While the small sample size of this uncontrolled study limits direct comparisons to findings in other studies, these findings suggest that crestal bone loss around TM implants is lower than traditional titanium implant systems [13,14], and that the unique properties of PTTM may foster enhanced vital bone and surrounding tissue ingrowth and potentially reduce the amount of bone remodeling which occurs during the first year following implant surgery [15].…”
Section: Discussionmentioning
confidence: 99%
“…RFA was chosen as a non-invasive and reliable method to assess variation in implant stability over time. RFA registrations are directly related to the stability of the implant in the surrounding bone: during healing an increase in implant stability quotient (ISQ) values presumably reflect new bone apposition at the implant-bone interface (28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that there were changes in the marginal bone level and loss of different amount of bone that occur mostly during the first year of dental implant placement [11][12][13]. Assessment of changes in marginal bone height is considered an important parameter in evaluating implant success [14,15].…”
Section: Introductionmentioning
confidence: 99%